Low plasma adiponectin levels in panic disorder - Unsal, Cuneyt; Hariri, Aytul Gursu; Yanartas, Omer; Sevinc, Ergun; Atmaca, Murad; Bilici, Mustafa (Elsevier, 2012)
Background: The present study was performed to evaluate plasma adiponectin levels in the patients with PD. Method: The study group included a total of 28 patients (17 females, 11 males) and 23 age- and sex-matched healthy comparison subjects (10 females and 13 males). The plasma fasting glucose, total cholesterol, triglyceride, low density lipoprotein (LDL), high density lipoprotein (HDL), and hemoglobin were measured. Results: There were no differences in regard to plasma fasting glucose, total cholesterol, triglyceride, LDL, HDL, and hemoglobin levels between groups. However, the mean adiponectin levels were significantly lower in the patient group (26.96 +/- 9.92 ng/ml) compared to controls (37.63 +/- 23.17 ng/ml) (t=-2.21; p =0.032). As for the ANCOVA analyses, it revealed the main effect of diagnosis on adiponectin levels (F=5.78, p=0.020) after BMI (body mass index) and gender as covariates. Conclusions: Consequently, the findings of our study suggest that there may be an interaction between panic disorder and plasma adiponectin. Moreover, they led us to consider that these patients should be also followed as cardiac problems. (C) 2012 Elsevier BM. All rights reserved.
Keywords: Panic disorder; Adiponectin; Glucose; Triglyceride